Effects of post weld heat treatments on the microstructure and mechanical properties of dissimilar weld of supermartensític stainless steel - Sérgio Souto Maior Tavares; Clóvis Ribeiro Rodrigues; Juan Manuel Pardal; Edvan da Silva Barbosa; Hamilton Ferreira Gomes de Abreu (Materials Research, 2014)
A supermartensitic stainless steel with composition 12.2%Cr-5.8%Ni-1.90%Mo-0.028%C (%wt.) was welded by gas tungsten arc welding (GTAW) with superduplex stainless steel filler metal. Post weld heat treatments (PWHT) at 650 ºC for different periods of time were performed in order to decrease the hardness in the heat affected zone (HAZ). This paper deals with the effect of these heat treatments on the microstructure and mechanical properties of the joint. Mechanical strength of the weld joint was slightly inferior to the base metal, but was not affected by heat treatments. Precipitation of intermetallic phases in the weld metal (WM) due to prolonged PWHT was detected by scanning electron microscopy. The impact toughness of the weld metal decreased with the increase of time of heat treatment, due to intermetallic precipitation. However, even in the specimen treated for 1h, the Charpy energy remained above 27J at -46 ºC. It was found that optimum mechanical properties can be obtained with heat treatment for 30 minutes at 650 ºC.